HUBUNGAN UJIAN BERBASIS KOMPUTER, KESIAPAN BELAJAR DENGAN PRESTASI BELAJAR DI SMK KETOPONG TENGGARONG - Zainuri, Habib (Fakultas Agama Islam Universitas Kutai Kartanegara Tenggarong, 2019)
The first hypothesis obtained t-count -0.732 <ttabel 1.668. other than based on sig value. of 0.466> 0.05, so it can be concluded that Ho accepted and Ha rejected and partially can be interpreted also that the relationship between variables X1 with Y of 0.083 which means the implementation of computer-based test are low correlated with learning achievement in SMK Ketopong Tenggarong. The second hypothesis obtained t-count -0.274 <ttabel 1.668. other than based on sig value. of 0.785> 0.05, so it can be concluded that Ho accepted and Ha rejected, partially the relationship between variables X2 with Y of 0.031 which means readiness correlates low with learning achievement in SMK Ketopong Tenggarong. In testing the third hypothesis obtained value Fcount 0.408 and table Ftabel distribution of 3.15. Since F = 0.408 <F0,05; 2.77 = 3.15, then H0 is accepted. At the level of significance obtained Sig = 0.667 and Î± = 0.05, because Î± = 0,05 <Sig = 0,000, then H0 is accepted. Together the relationship between the variable implementation of computer-based test and readiness to learn with learning achievement of 0.102 which means the implementation of computer-based test and study readiness correlates low with learning achievement in SMK Ketopong Tenggarong Teaching Year 2016-2017. This it can be concluded that the implementation of computer-based test variables is low correlated with learning achievement. Whereas Learning Readiness variable correlate low with learning achievement. And the third hypothesis that there is a low relationship between the implementation of computer-based test and readiness to learn with student achievement SMK Ketopong Tenggarong academic year 2016-2017.